2021
DOI: 10.1128/mbio.00143-21
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the Four Essential Entry Glycoproteins to HSV-1 Tropism and the Selection of Entry Routes

Abstract: Herpes simplex viruses (HSV-1 and HSV-2) encode up to 16 envelope proteins, four of which are essential for entry. However, whether these four proteins alone are sufficient to dictate the broad cellular tropism of HSV-1 and the selection of different cell type-dependent entry routes is unknown. To begin addressing this, we previously pseudotyped vesicular stomatitis virus (VSV), lacking its native glycoprotein G, with only the four essential entry glycoproteins of HSV-1: gB, gH, gL, and gD. This novel VSVΔG-BH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 111 publications
1
12
0
Order By: Relevance
“…2A and D ). Since HSV-1 enters most known target cell types by pH-dependent endocytosis (10, 11, 57, 58), we tested pH ranging from pH 6.5 to 4.5 by adding predetermined amounts of HCl after incubation with a soluble receptor. Upon acidification in the presence of HVEM200t-His 8 , we observed robust fusion at pH <5.5, ∼40% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2A and D ). Since HSV-1 enters most known target cell types by pH-dependent endocytosis (10, 11, 57, 58), we tested pH ranging from pH 6.5 to 4.5 by adding predetermined amounts of HCl after incubation with a soluble receptor. Upon acidification in the presence of HVEM200t-His 8 , we observed robust fusion at pH <5.5, ∼40% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test whether these four glycoproteins were sufficient for in-vitro fusion, we generated VSV virions lacking the native fusogen G and pseudotyped with HSV-1 gB, gH, gL, and gD (VSVΔG-BHLD). Previously, we showed that these VSVΔG-BHLD pseudotypes entered two types of HSV-1-susceptible cells (57, 88). Here, we found that the VSVΔG-BHLD pseudotypes fused with the target BMP LUVs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HSV-1 entry needs four glycoproteins: -gB, gH, gL, and gD-. [ 17 ]. Therefore, it is possible that the inhibitory effect of officinaloside C on viral replication is due to the inhibition of gB expression.…”
Section: Resultsmentioning
confidence: 99%
“…There are few if any host cell processes known to mediate the initial internalization step of HSV entry. Endocytic uptake of HSV can occur independently of clathrin, caveolin, cholesterol, and dynamin ( 22 , 68 , 92 97 ). We show that neddylation is integral to internalization of HSV-1 by endocytosis in B78-nectin-1 cells and human HaCaT cells.…”
Section: Discussionmentioning
confidence: 99%